2008
DOI: 10.1002/anie.200801510
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Enantioselective Trapping of an Alcoholic Oxonium Ylide with Aldehydes: RhII/ZrIV‐Co‐Catalyzed Three‐Component Reactions of Aryl Diazoacetates, Benzyl Alcohol, and Aldehydes

Abstract: The right combination: A catalytic asymmetric multicomponent reaction has been developed in which two stereogenic carbon centers are constructed in a single step (see scheme; erythro/threo 90:10, up to 80 % yield, 98 % ee). This type of enantioselective three‐component reaction generates α,β‐dihydroxy acid derivatives in good yields and with excellent enantioselectivities. Bn=benzyl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(21 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…Unfortunately, Use of acetaldehyde (and sometimes other aliphatic aldehydes) in many MCRs is not always as straightforward as that of aromatic aldehydes. There are plentiful reports where many common MCR sequences either failed or resulted in lower yield of products when attempted with acetaldehyde /aliphatic aldehydes . This may be due to their different reactivity profile than aromatic aldehydes, higher sensitivity towards self‐polymerization, low stability and competitive isomerisation of the resultant imine (with an amine) to an enamine.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, Use of acetaldehyde (and sometimes other aliphatic aldehydes) in many MCRs is not always as straightforward as that of aromatic aldehydes. There are plentiful reports where many common MCR sequences either failed or resulted in lower yield of products when attempted with acetaldehyde /aliphatic aldehydes . This may be due to their different reactivity profile than aromatic aldehydes, higher sensitivity towards self‐polymerization, low stability and competitive isomerisation of the resultant imine (with an amine) to an enamine.…”
Section: Introductionmentioning
confidence: 99%
“…[9] In particular, transition-metalcatalyzed reactions of diazo compounds have been highly successful. [11,12] In addition, the situ-generation of sulfur ylides from diazo compounds and sulfide has been well documented for the construction of CÀ S and CÀ C bond [13,14] via the Doyle-Kirmse [15] or Stevens [16] rearrangement reaction. [11,12] In addition, the situ-generation of sulfur ylides from diazo compounds and sulfide has been well documented for the construction of CÀ S and CÀ C bond [13,14] via the Doyle-Kirmse [15] or Stevens [16] rearrangement reaction.…”
mentioning
confidence: 99%
“…Screening of copper catalysts revealed that Cu(OTf) 2 was optimal one (entries [2][3][4][5]. Solvent effects have also been observed, and the reaction proceeded well in DCE, while DMF, THF and CH 3 CN are not suitable for this reaction (Table 1, entries [12][13][14]. Solvent effects have also been observed, and the reaction proceeded well in DCE, while DMF, THF and CH 3 CN are not suitable for this reaction (Table 1, entries [12][13][14].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We initiated our study by examining the reaction of methyl phenyldiazoacetate, benzyl alcohol, and readily available methyl cinnamate (1a) in the presence of Rh 2 (OAc) 4 in CH 2 Cl 2 at 25°C. 8 Unfortunately, no desired three-component product was observed, instead only a traditional O-H insertion of the diazo compound into benzyl alcohol took place.…”
mentioning
confidence: 99%